Ultrasound-guided serratus posterior superior muscle block for myofascial pain syndrome in the cervicoscapular region: a report of three cases - Atsushi Sawada; Michiaki Yamakage (JA Clinical Reports)
Abstract Background These case reports focus on successful pain management with ultrasound-guided serratus posterior superior muscle (SPSM) block using 30 mL of 0.25% ropivacaine or physiological saline in three myofascial pain syndrome (MPS) patients presented with cervicoscapular pain. Case presentation The SPSM block was administered to three ambulatory patients (cases #1, #2, and #3) who presented with cervicoscapular pain. The SPSM block with 30 mL of 0.25% ropivacaine drastically decreased an NRS score and provided 2–3 weeks of pain relief in cases #1 and #2. On the contrary, the SPSM block with 30 mL of physiological saline also mildly decreased an NRS score and provided 3 weeks of pain relief in cases #1 and #3. Conclusions The SPSM block using 30 mL of 0.25% ropivacaine or physiological saline successfully decreased the NRS scores in three MPS patients. These findings suggest that the SPSM block may serve as a useful therapeutic option in MPS patients presenting with cervicoscapular pain.